Legal Analysis of Contract Change Orders (CCO) Affecting Addendums in Construction Contracts - Rosiana Agnes Rizky; Martono Anggusti; Jinner Sidauruk (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the influence of Contract Change Order (CCO) on addendum in a contract, focusing on the legal aspects and practical implications in the implementation of construction projects. CCO is an important instrument that allows changes in the scope, cost, and time of a project, which can lead to the issuance of an addendum. Through a juridical-normative approach and case study analysis of the Diponegoro Street Widening and Overlay project in Sragen, this study found that CCO has significant legal power in influencing addendum. The results show that CCO not only affects the cost and time of implementation but also the quality of the final project results. The addendum process is crucial to ensure that all changes are officially recorded, as well as to maintain compliance with applicable regulations. This study concludes that effective change management through CCO and addendum is key to achieving construction project success.